Effects of a concurrent task on fixed-interval responding in humans - Laties, Victor G. (1963)
Subjects pressed a telegraph key to illuminate a meter dial on which pointer deflections appeared at fixed intervals. Upon detecting a deflection they were required to press another key to reset the pointer to zero. This detecting and resetting operation reinforced the behavior of pressing the light-flashing key (i.e., the observing responses). The usual pattern of responding on the light-flashing key was a long pause following the reinforcement and an abrupt transition to a steady response rate toward the end of the interval. When the subjects were required to perform a concurrent subtraction task, the pattern of responding changed in varying degrees, ranging from complete loss of typical fixed-interval behavior to a slight shortening of the post-reinforcement pause. These effects were attributed to the disruption of the self-produced verbal chains (counting or reciting) that ordinarily govern human behavior on this schedule.